ANALISIS KEMAMPUAN MENULIS KARANGAN DESKRIPSI PADA SISWA KELAS V MENGGUNAKAN PEMBELAJARAN MODEL DARING DI SEKOLAH DASAR NEGERI 39 PONTIANAK KOTA - Anita Sari Surveyati; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe study aims to analyze a student's ability to write a description essay. The methodused in this study is a qualitative descriptive method. The object of this study is thestudent's essay that is assessed from the titlebook's content, spelling, diction, sentencestructure, interdepartmental sentences, interdepartmental paragraphs, overallcontent, and orderliness. The source of data for the study is the 39th country's B.S.D.'s poll of 31 students. It enhances interviews, documentaries. This study suggests thatthe average descriptive writing ability is that 75 falls in category (good). Thepercentage of students is seen in terms of a very good 2 person or 0.6% category,either 14 person category or 0.45%, enough category 13 person or 0.43%, less 2person or 0.6%. The difficulties students encounter are several aspects of the use andspelling of spelling (use of capital letters, punctuation, writing words that are lessletters, connecting signs), overall content, sentence structure, paragraph alignment(difficult to develop a paragraph or less able to suspend an idea). Thus, it may beconcluded that the ability to write a description on class vb specifies the learning ofonline models is sufficient because there are still some of the students' difficulties inwriting the description.Keywords: writing ability, made-up description, online learnin.